Multilayered metal foil, conductive filler, and conductive material

A multi-layered metal foil structure with gold and silver layers, supplemented by copper, addresses the high cost of precious metals in conductive inks, enhancing chemical stability and reducing material costs while maintaining conductivity.

JP2025017337AActive Publication Date: 2025-02-05JAPAN ADVANCED INST OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024114652
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-24
Filing Date
2024-07-18
Publication Date
2025-02-05
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

The high cost of precious metals like silver, gold, and platinum, along with the lack of examination on alternative materials, hinders the development of conductive inks for printed circuit boards, necessitating a solution that enhances chemical stability while reducing raw material costs.

Method used

A multi-layered metal foil structure comprising different metals in each layer, such as gold and silver, with a copper layer for cost reduction, improves chemical stability and conductivity.

Benefits of technology

The multi-layered metal foil structure achieves enhanced chemical stability and reduced raw material costs, enabling efficient conductive filler and material performance in conductive inks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017337000001_ABST
    Figure 2025017337000001_ABST
Patent Text Reader

Abstract

To provide a metal foil excellent in chemical stability and suitable for reducing a raw material cost.SOLUTION: A multilayered metal foil comprises a first metal layer 11, a second metal layer 12, and a third metal layer 13 disposed between the first metal layer 11 and the second metal layer 12, wherein: the metal M2 contained as a main component in the second metal layer 12 is the same as or different from the metal M1 contained as a main component in the first metal layer 11; and the metal M3 contained as the main component in the third metal layer 13 is a multilayered metal foil that is different from metals M1 and M2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to multilayer metal foils, conductive fillers, and conductive materials. [Background technology]

[0002] In recent years, the development of conductive inks for use in printed circuit boards for electronic devices has been actively promoted. Conductive inks contain metal particles as conductive fillers. Silver particles are often used as the metal particles.

[0003] The conductivity of the conductive film obtained by drying the conductive ink is expressed by contact between the metal particles. Therefore, it is important to ensure good contact between the metal particles. For example, flake-shaped metal particles are preferable as conductive particles because they can ensure a larger contact area than metal particles with needle-like or other shapes.

[0004] Patent Documents 1 and 2 disclose conductive inks that use flake-shaped silver particles as a conductive filler. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2011-195695 A [Patent Document 2] JP 2015-157941 A Summary of the Invention [Problem to be solved by the invention]

[0006] Considering the chemical stability of the conductive film, it is desirable to use precious metals such as silver, gold, platinum, etc., which have excellent chemical stability, as the raw material for the conductive filler. However, at present, the need to reduce the raw material cost even for silver fine particles is emphasized, and concrete consideration has hardly progressed regarding the use of raw materials such as gold and platinum, which are even more expensive than silver.

[0007] An object of the present invention is to provide a metal foil which is excellent in chemical stability and is suitable for reducing raw material costs. [Means for solving the problem]

[0008] The present invention relates to a first metal layer, a second metal layer, and a third metal layer disposed between the first metal layer and the second metal layer; a metal contained as a main component in the second metal layer is the same as or different from a metal contained as a main component in the first metal layer; a metal contained as a main component in the third metal layer is different from the metal contained as a main component in the first metal layer and the metal contained as a main component in the second metal layer; multilayer metal foil, to provide.

[0009] The present invention also relates to a conductive filler, which is a metal fine particle made of the multilayer metal foil of the present invention; to provide.

[0010] Furthermore, the present invention relates to a conductive material comprising the conductive filler of the present invention. to provide. Effect of the Invention

[0011] According to the present invention, it is possible to provide a metal foil that is excellent in chemical stability and is suitable for reducing raw material costs. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic perspective view of an example of a multilayer metal foil according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of the multilayer metal foil of FIG. [Diagram 3] FIG. 2 is a schematic cross-sectional view of another example of a multilayer metal foil according to the present invention. [Figure 4] FIG. 1 is a schematic cross-sectional view of an example of a conductive film according to the present invention. [Diagram 5] FIG. 2 is a schematic cross-sectional view of another example of a conductive film according to the present invention. [Figure 6] FIG. 2 is a schematic cross-sectional view for explaining the dispersion state of a conductive filler in a film. [Figure 7A] 4 is a schematic cross-sectional view for explaining an angle θ between a perpendicular line to a main surface of a conductive filler and a thickness direction of a film. FIG. [Figure 7B] 7B is a schematic cross-sectional view for explaining the angle θ, similar to FIG. 7A. [Figure 8] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 1 by transmission electron microscopy (TEM) (magnification: 300,000 times). [Figure 9] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 2 with a TEM (magnification: 800,000 times). [Figure 10] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 3 with a TEM (magnification: 300,000 times). [Figure 11] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 4 with a TEM (magnification: 300,000 times). [Figure 12] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 5 with a TEM (magnification: 300,000 times). [Figure 13] 1 is a diagram showing the results of TEM observation of a cross section of the multilayer metal foil of Example 6 (magnification: 1,000,000 times). [Figure 14] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 7 with a TEM (magnification: 300,000 times). [Figure 15] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 8 with a TEM (magnification: 300,000 times). [Figure 16] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 9 with a TEM (magnification: 300,000 times). [Figure 17] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 10 with a TEM (magnification: 300,000 times). [Figure 18]1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 11 with a TEM (magnification: 300,000 times). [Figure 19] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 12 with a TEM (magnification: 300,000 times). [Figure 20] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 13 with a TEM (magnification: 300,000 times). [Figure 21] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 14 with a TEM (magnification: 300,000 times). [Figure 22] FIG. 1 shows the results of observing a cross section of the multilayer metal foil of Example 15 with a TEM (magnification: 300,000 times). [Figure 23] FIG. 1 shows the results of observing a cross section of the multilayer metal foil of Example 16 with a TEM (magnification: 600,000 times). [Figure 24] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 17 with a TEM (magnification: 400,000 times). [Diagram 25] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 18 with a TEM (magnification: 300,000 times). [Figure 26] 1 is a diagram showing the results of observing a cross section of the multilayer metal foil of Example 19 with a TEM (magnification: 600,000 times). [Figure 27] FIG. 2 is a diagram showing the results of observing the main surfaces of the multilayer metal foils of Examples 1 and 2. [Figure 28] FIG. 2 is a diagram showing the results of observing the main surfaces of the multilayer metal foils of Examples 3 and 4. [Figure 29] FIG. 2 is a diagram showing the results of observing the main surfaces of the multilayer metal foils of Examples 5 and 6. [Diagram 30] FIG. 13 is a diagram showing the results of observing the main surface of the multilayer metal foil of Example 7. [Diagram 31] FIG. 1 shows the results of observing the main surfaces of the multilayer metal foils of Examples 8 and 9. [Diagram 32] FIG. 13 is a diagram showing the results of observing the main surface of the multilayer metal foil of Example 10. [Diagram 33] FIG. 1 shows the results of observing the main surfaces of the multilayer metal foils of Examples 11 and 12. [Diagram 34] FIG. 13 is a diagram showing the results of observing the main surface of the multilayer metal foil of Example 13. [Diagram 35] FIG. 1 shows the results of observing the main surfaces of the multilayer metal foils of Examples 14 and 15. [Diagram 36] FIG. 2 is a diagram showing the results of observing the main surfaces of the multilayer metal foils of Examples 16 and 17. [Figure 37] FIG. 2 is a diagram showing the results of observing the main surfaces of the multilayer metal foils of Examples 18 and 19. [Figure 38] 13 is a graph showing the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive films of Examples 20 and 21 and the sheet resistance of the conductive films of Examples 20 and 21. [Figure 39] 13 is a graph showing the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive films of Examples 22 and 23 and the sheet resistance of the conductive films of Examples 22 and 23. [Diagram 40] 13 is a graph showing the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive films of Examples 24 and 25 and the sheet resistance of the conductive films of Examples 24 and 25. [Diagram 41] 13 is a graph showing the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive films of Examples 26 to 28 and the sheet resistance of the conductive films of Examples 26 to 28. [Diagram 42] 13 is a graph showing the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive films of Examples 29 and 30 and the sheet resistance of the conductive films of Examples 29 and 30. [Diagram 43] 13 is a graph showing the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive films of Examples 31 and 32 and the sheet resistance of the conductive films of Examples 31 and 32. [Diagram 44] 13 is a graph showing the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive films of Reference Examples 5 to 8 and the sheet resistance of the conductive films of Reference Examples 5 to 8. [Diagram 45]1 is a graph showing the relationship between the number of days stored in the atmosphere at room temperature and the sheet resistance of the conductive films of Reference Examples 9 to 12. [Figure 46] 13 is a graph showing the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive films of Example 33, Reference Examples 5 and 8, and the sheet resistance of the conductive films of Example 33, Reference Examples 5 and 8. [Figure 47] 13 is a graph showing the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive films of Example 34, Reference Examples 6 and 8, and the sheet resistance of the conductive films of Example 34, Reference Examples 6 and 8. [Figure 48] 13 is a graph showing the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive films of Example 35, Reference Examples 7 and 8, and the sheet resistance of the conductive films of Example 35, Reference Examples 7 and 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The multilayer metal foil according to the first aspect of the present invention is a first metal layer, a second metal layer, and a third metal layer disposed between the first metal layer and the second metal layer; a metal contained as a main component in the second metal layer is the same as or different from a metal contained as a main component in the first metal layer; The metal contained as a main component in the third metal layer is different from the metal contained as a main component in the first metal layer and the metal contained as a main component in the second metal layer.

[0014] In the second aspect of the present invention, for example, in the multilayer metal foil according to the first aspect, The standard electrode potential of the metal contained as a main component in the first metal layer and the metal contained as a main component in the second metal layer is greater than the standard electrode potential of the metal contained as a main component in the third metal layer.

[0015] In a third aspect of the present invention, for example, in the multilayer metal foil according to the first or second aspect, The first metal layer and the second metal layer satisfy one selected from the group consisting of the following (I) to (III). (I) The metal contained as a main component in the first metal layer and the metal contained as a main component in the second metal layer are gold. (II) The metal contained as a main component in the first metal layer and the metal contained as a main component in the second metal layer are silver. (III) The metal contained as a main component in the first metal layer is gold, and the metal contained as a main component in the second metal layer is silver.

[0016] In the fourth aspect of the present invention, for example, in the multilayer metal foil according to the third aspect, The third metal layer satisfies the following (i) or (ii). (i) When the first metal layer and the second metal layer satisfy the condition (I), the metal contained as a main component in the third metal layer is silver or copper. (ii) When the first metal layer and the second metal layer satisfy the condition (II) or (III), the metal contained as a main component in the third metal layer is copper.

[0017] In a fifth aspect of the present invention, for example, in the multilayer metal foil according to any one of the first to fourth aspects, The metal contained as a main component in the first metal layer is the same as the metal contained as a main component in the second metal layer.

[0018] In the sixth aspect of the present invention, for example, in the multilayer metal foil according to the fifth aspect, The content of the metal contained as a main component in the first metal layer is different from the content of the metal contained as a main component in the second metal layer.

[0019] In a seventh aspect of the present invention, for example, in the multilayer metal foil according to any one of the first to sixth aspects, The third metal layer may be composed of a single layer or multiple layers.

[0020] In an eighth aspect of the present invention, for example, in the multilayer metal foil according to any one of the first to seventh aspects, The third metal layer has a thickness greater than the thicknesses of the first metal layer and the second metal layer.

[0021] A conductive filler according to a ninth aspect of the present invention is metal fine particles made of the multilayer metal foil according to any one of the first to eighth aspects.

[0022] In a tenth aspect of the present invention, for example, in the conductive filler according to the ninth aspect, In the metal fine particles, the chemical stability of the first metal layer and the chemical stability of the second metal layer are higher than the chemical stability of the third metal layer.

[0023] In an eleventh aspect of the present invention, for example, in the conductive filler according to the ninth or tenth aspect, In the metal fine particles, the conductivity of the first metal layer and the conductivity of the second metal layer are lower than the conductivity of the third metal layer.

[0024] In the twelfth aspect of the present invention, for example, in the conductive filler according to the ninth or tenth aspect, In the metal fine particles, the first metal layer and the second metal layer have a higher electrical conductivity than the third metal layer.

[0025] A conductive material according to a thirteenth aspect of the present invention includes the conductive filler according to any one of the ninth to twelfth aspects.

[0026] The present invention will now be described in detail, but the following description is not intended to limit the present invention to a specific embodiment.

[0027] [Multilayer metal foil] Fig. 1 is a schematic perspective view of an example of a multilayer metal foil 10 according to the present invention. Fig. 2 is a schematic cross-sectional view of the multilayer metal foil 10. The multilayer metal foil 10 has a pair of parallel principal surfaces 10a and 10b. The distance between the principal surfaces 10a and 10b corresponds to the thickness t10 of the multilayer metal foil 10. Since the multilayer metal foil 10 is foil-shaped, when it is used as a conductive filler, for example, it is likely to come into contact with each other in a conductive film not at points but at surfaces, which is advantageous for forming a conductive path compared to needle-shaped or other shapes.

[0028] The multi-layer metal foil 10 comprises a first metal layer 11, a second metal layer 12, and a third metal layer 13 disposed between the first metal layer 11 and the second metal layer 12. In this disclosure, "multi-layer" refers to a structure having multiple layers.

[0029] The multilayer metal foil 10 may include any metal layer other than the first metal layer 11, the second metal layer 12, and the third metal layer 13. From the viewpoints of raw material costs and productivity, it is preferable that the multilayer metal foil 10 does not include any metal layer other than the first metal layer 11, the second metal layer 12, and the third metal layer 13. That is, as shown in FIG. 2, the multilayer metal foil 10 may be composed of only the first metal layer 11, the second metal layer 12, and the third metal layer 13.

[0030] The metal contained as a main component in the first metal layer 11 is defined as metal M1. The metal contained as a main component in the second metal layer 12 is defined as metal M2. The metal contained as a main component in the third metal layer 13 is defined as metal M3. In this disclosure, "main component" means the component contained in the largest amount by mass ratio.

[0031] In the multilayer metal foil 10, the metal M2 is the same as or different from the metal M1. In the multilayer metal foil 10, the metal M3 is different from the metal M1 and the metal M2.

[0032] Precious metals such as silver, gold, and platinum have excellent chemical stability. Therefore, for example, by using precious metals such as silver, gold, and platinum as the metal M1 and the metal M2, the chemical stability of the multilayer metal foil 10 can be improved. In addition, for example, by using precious metals such as silver, gold, and platinum as the metal M1 and the metal M2 and using copper as the metal M3, the raw material cost can be reduced compared to a metal foil made only of precious metals such as silver, gold, and platinum. That is, the multilayer metal foil 10 can realize a metal foil that has excellent chemical stability and is suitable for reducing raw material costs. The multilayer metal foil 10 is useful, for example, as a conductive filler.

[0033] Furthermore, precious metals such as silver, gold, and platinum have better oxidation resistance than, for example, copper, and therefore, for example, by using precious metals such as silver, gold, and platinum as the metal M1 and the metal M2 and using copper as the metal M3, the oxidation resistance of the multilayer metal foil 10 can be improved.

[0034] Furthermore, in the multilayer metal foil 10, the colors that appear on the main surfaces 10a and 10b can be changed in various ways depending on the metals M1, M2, and M3 used. Therefore, the multilayer metal foil 10 can realize metal foils with unprecedented color shades.

[0035] The standard electrode potentials of metal M1 and metal M2 are preferably greater than the standard electrode potential of metal M3.

[0036] The standard electrode potential of a metal can be one of the indicators of the chemical stability of the metal. The larger the standard electrode potential, the higher the chemical stability can be considered. Therefore, if the standard electrode potential of the metal M1 and the metal M2 is higher than the standard electrode potential of the metal M3, the chemical stability of the multilayer metal foil 10 can be improved. Examples of the multilayer metal foil 10 having such a configuration include a multilayer metal foil 10 using gold as the metal M1 and the metal M2 and silver or copper as the metal M3, a multilayer metal foil 10 using silver as the metal M1 and the metal M2 and copper as the metal M3, and a multilayer metal foil 10 using gold as the metal M1, silver as the metal M2, and copper as the metal M3. The standard electrode potential of gold is 1.50V. The standard electrode potential of silver is 0.80V. The standard electrode potential of copper is 0.34V.

[0037] It is preferable that the first metal layer 11 and the second metal layer 12 satisfy one selected from the group consisting of the following (I) to (III). (I) Metal M1 and metal M2 are gold. (II) Metal M1 and metal M2 are silver. (III) The metal M1 is gold and the metal M2 is silver.

[0038] When the first metal layer 11 and the second metal layer 12 satisfy one selected from the group consisting of the above (I) to (III), it is possible to improve the chemical stability of the multilayer metal foil 10. In addition, for example, by using copper as the metal M3, it is possible to reduce the raw material cost.

[0039] It is more preferable that the first metal layer 11 and the second metal layer 12 satisfy the above (I) or (III), and furthermore preferable that they satisfy the above (I). Gold is a precious metal with the best malleability. Therefore, by using gold, the flexibility of the multilayer metal foil 10 and the ability to absorb stress due to deformation are improved. Such characteristics of gold are suitable for, for example, ensuring contact between metal particles in a conductive film, that is, forming and maintaining a conductive path. In addition, gold has higher oxidation resistance than silver, and an oxide layer is not formed on the surface. Therefore, especially when the above (I) is satisfied, a conductive path can be easily formed even if the conductive ink is dried at a low temperature (for example, about 40 to 60°C, or in some cases, room temperature). The ability to form a conductive path at such a low temperature is an advantageous feature that enables the formation of a conductive film on a substrate or a substitute thereof with low heat resistance, specifically paper, clothing, etc., and in some cases, direct formation of a film on human skin. On the other hand, the price of gold is several tens of times higher than the price of silver. However, when the multilayer metal foil 10 satisfies the above (I) or (III), for example, by using copper as the metal M3 contained as the main component in the third metal layer 13, the raw material costs can be reduced compared to a metal foil consisting only of gold.

[0040] When the metal M1 contained as a main component in the first metal layer 11 is gold, the first metal layer 11 may contain elements other than gold, such as silver, platinum, palladium, rhodium, iridium, ruthenium, osmium, copper, zinc, tin, iron, nickel, cobalt, chromium, titanium, magnesium, aluminum, indium, sodium, calcium, carbon, oxygen, silicon, etc. The same applies when the metal M2 contained as a main component in the second metal layer 12 is gold.

[0041] When the first metal layer 11 and the second metal layer 12 satisfy the above (I) or (III), from the viewpoint of raw material costs, the metal M1 and the metal M2 may contain elements other than gold. The elements other than gold are not particularly limited and may be, for example, the elements from silver to silicon listed above, but are preferably silver and / or copper. The content of the elements other than gold is, for example, 0.1 mass% or more, further 0.3 mass% or more, and in some cases 0.5 mass% or more. The upper limit of the content of the elements other than gold is not particularly limited as long as gold is the main component, but is, for example, 45 mass% or less, particularly 10 mass% or less.

[0042] The compositions of alloys that are particularly suitable for the metal M1 and the metal M2 are shown below, although the compositions of the alloys that constitute the metal M1 and the metal M2 are not limited to the compositions shown below. Gold: 50~99.9% by mass Silver: 0.1~45% by mass Copper: 0~5% by mass

[0043] When the metal M1 contained as a main component in the first metal layer 11 is silver, the first metal layer 11 may contain elements other than silver, such as gold, platinum, palladium, rhodium, iridium, ruthenium, osmium, copper, zinc, tin, iron, nickel, cobalt, chromium, titanium, magnesium, aluminum, indium, sodium, calcium, carbon, oxygen, silicon, etc. The same applies when the metal M2 contained as a main component in the second metal layer 12 is silver.

[0044] It is preferable that the third metal layer 13 satisfies the following (i) or (ii). (i) When the first metal layer 11 and the second metal layer 12 satisfy the above (I), the metal M3 is silver or copper. (ii) When the first metal layer 11 and the second metal layer 12 satisfy the above (II) or (III), the metal M3 is copper.

[0045] When the third metal layer 13 satisfies the above (i) or (ii), the chemical stability of the multilayer metal foil 10 can be improved and the raw material costs can be reduced.

[0046] It is more preferable that the third metal layer 13 satisfies the above condition (ii). When the metal M3 contained as a main component in the third metal layer 13 is copper, the raw material cost of the multilayer metal foil 10 can be further reduced.

[0047] When the metal M3 contained as the main component in the third metal layer 13 is silver, the third metal layer 13 may contain elements other than silver, such as gold, platinum, palladium, rhodium, iridium, ruthenium, osmium, copper, zinc, tin, iron, nickel, cobalt, chromium, titanium, magnesium, aluminum, indium, sodium, calcium, carbon, oxygen, silicon, etc.

[0048] When the metal M3 contained as a main component in the third metal layer 13 is copper, the third metal layer 13 may contain elements other than copper, such as silver, gold, platinum, palladium, rhodium, iridium, ruthenium, osmium, zinc, tin, iron, nickel, cobalt, chromium, titanium, magnesium, aluminum, indium, sodium, calcium, carbon, oxygen, silicon, etc. When the metal M3 is copper, the alloy constituting the metal M3 may be brass containing zinc. The brass may be red brass (zinc: 4 to 22 mass %).

[0049] Metal M1 may be the same as metal M2. For example, as described in (I) above, metal M1 and metal M2 may both be gold. For example, as described in (II) above, metal M1 and metal M2 may both be silver.

[0050] According to this configuration, it is easy to realize a metal foil that has excellent chemical stability and is suitable for reducing raw material costs.

[0051] Metal M1 may be different from metal M2. For example, metal M1 may be gold and metal M2 may be silver, as described in (III) above. Of course, metal M1 may be silver and metal M2 may be gold.

[0052] With such a configuration, it is easy to realize a metal foil that is excellent in chemical stability and suitable for reducing raw material costs. In addition, the color that appears on the main surface 10a can be made different from the color that appears on the main surface 10b.

[0053] The mass content of metal M1 contained as a main component in first metal layer 11 is defined as content R1. The mass content of metal M2 contained as a main component in second metal layer 12 is defined as content R2. The mass content of metal M3 contained as a main component in third metal layer 13 is defined as content R3. Contents R1, R2, and R3 may be 50 mass% or more, further 70 mass% or more, and in some cases 90 mass% or more.

[0054] When the contents R1, R2, and R3 are within the above numerical ranges, for example, the multilayer metal foil 10 can exhibit excellent electrical conductivity when used as a conductive filler.

[0055] The content rate R1 and the content rate R2 may be different. The content rate R1 may be greater than the content rate R2, or the content rate R2 may be greater than the content rate R1.

[0056] According to such a configuration, even if the metal M1 and the metal M2 are the same metal, for example, it may be possible to make the color expressed on the main surface 10a different from the color expressed on the main surface 10b. Also, the metal M1 and the metal M2 can be selected according to the budget.

[0057] As shown in FIG. 2, the thickness t13 of the third metal layer 13 is preferably greater than the thickness t11 of the first metal layer 11 and the thickness t12 of the second metal layer 12.

[0058] Such a structure makes it easy to realize a metal foil that is suitable for reducing raw material costs while improving the chemical stability of the multilayer metal foil 10.

[0059] The thickness t10 of the multilayer metal foil 10 is not particularly limited and can be appropriately set depending on the application. The thickness t10 of the multilayer metal foil 10 is, for example, 100 nm or more and 10 μm or less. The thickness t10 of the multilayer metal foil 10 may be 5 μm or less.

[0060] The multilayer metal foil 10 having such a structure is useful, for example, as a conductive filler, and is also useful as a metal foil having a color that has never been seen before.

[0061] When used as a conductive filler, the thickness t10 of the multilayer metal foil 10 may be 100 nm or more and 1 μm or less, or may be 100 nm or more and 500 nm or less.

[0062] The thickness t10 of the multilayer metal foil 10 can be determined by measuring the thickness of at least 30 sheets, preferably 100 sheets, of the multilayer metal foil 10 using a transmission electron microscope (TEM) and calculating the simple average.

[0063] The thickness t11 of the first metal layer 11 and the thickness t12 of the second metal layer 12 may be 1 nm or more and 80 nm or less. The thickness t11 of the first metal layer 11 and the thickness t12 of the second metal layer 12 may be the same or different. The thickness t11 of the first metal layer 11 and the thickness t12 of the second metal layer 12 can be determined by the same method as the thickness t10 of the multilayer metal foil 10.

[0064] The thickness t13 of the third metal layer 13 may be 80 nm or more and 5 μm or less. With such a structure, a metal foil suitable for reducing raw material costs can be realized. The thickness t13 of the third metal layer 13 can be determined by the same method as the thickness t10 of the multilayer metal foil 10.

[0065] In the multilayer metal foil 10 shown in Fig. 2, the third metal layer 13 is made of a single layer. However, the third metal layer 13 is not limited to a single layer. The third metal layer 13 may be made of multiple layers.

[0066] Fig. 3 is a schematic cross-sectional view of another example of the multilayer metal foil 10 according to the present invention. In the multilayer metal foil 10 shown in Fig. 3, the third metal layer 13 is made up of multiple metal layers 13a to 13e. With this structure, for example, it is easy to adjust the thickness t13 of the third metal layer 13.

[0067] 3, the number of metal layers constituting third metal layer 13 is five. However, the number of metal layers constituting third metal layer 13 is not particularly limited. The number of metal layers constituting third metal layer 13 may be, for example, 3 to 10, 4 to 9, or 5 to 8.

[0068] The thickness of each of the multiple metal layers constituting the third metal layer 13 may be 10 nm or more and 1 μm or less. The thickness of each of the multiple metal layers may be the same or different. The thickness of each of the multiple metal layers can be determined by the same method as the thickness t10 of the multilayer metal foil 10.

[0069] There is no particular limitation on the shape and size of the multilayer metal foil 10. The multilayer metal foil 10 may be approximately a square of 10 cm x 10 cm. The multilayer metal foil 10 may be approximately a square of 20 cm x 20 cm.

[0070] [Method of manufacturing multi-layer metal foil] The above-mentioned multilayer metal foil 10 can be produced, for example, by the following method.

[0071] A method for manufacturing the multilayer metal foil 10 includes, for example, placing a material for the third metal layer 13 between the material for the first metal layer 11 and the material for the second metal layer 12 to obtain a laminate (step S1), and rolling out the obtained laminate to a thickness of 100 nm or more and 10 μm or less (step S2).

[0072] The laminate obtained in step S1 has a roughly square shape of, for example, 10 cm x 10 cm.

[0073] Step S2 may be performed using a squeegee. In step S2, the laminate may be squeegeeed to reduce the thickness to about 1 / 12, thereby achieving a thickness of 100 nm to 10 μm.

[0074] Step S2 may include multiple sub-steps. For example, in a first sub-step, the laminate may be rolled out so that the thickness is reduced to about 1 / 3, and then the laminate may be cut into a substantially square shape of 10 cm x 10 cm. Next, in a second sub-step, the laminate may be rolled out so that the thickness is reduced to about 1 / 9 to 1 / 10, and then the laminate may be cut into a substantially square shape of 10 cm x 10 cm. Furthermore, in a third sub-step, the laminate may be rolled out so that the thickness is reduced to about 1 / 12. In this manner, a multilayer metal foil 10 having a thickness t10 of 100 nm or more and 10 μm or less may be obtained.

[0075] When the third metal layer 13 is a single layer, for example, in step S1, a 10 cm x 10 cm silver-finished product as the material for the third metal layer 13 may be placed between a 10 cm x 10 cm gold foil as the material for the first metal layer 11 and a 10 cm x 10 cm gold foil as the material for the second metal layer 12 to obtain a laminate. In this disclosure, "finished product" refers to a product that is a pre-process before being finished into a "foil." The "foil" is made by beating and stretching the "finished product." The thickness of the "foil" is about 1 / 10 of the thickness of the "finished product."

[0076] In step S2, the obtained laminate is rolled out, for example, to a thickness of 100 nm or more and 10 μm or less, thereby producing a multilayer metal foil 10 having gold foil as the first metal layer 11, gold foil as the second metal layer 12, and a single layer of silver foil as the third metal layer 13.

[0077] If the third metal layer 13 is a multi-layer structure, for example, in step S1, five pieces of silver foil measuring 10 cm x 10 cm as the material for the third metal layer 13 may be stacked between a gold foil measuring 10 cm x 10 cm as the material for the first metal layer 11 and a gold foil measuring 10 cm x 10 cm as the material for the second metal layer 12 to obtain a laminate.

[0078] In step S2, the obtained laminate is rolled out, for example, to a thickness of 100 nm or more and 10 μm or less, thereby producing a multilayer metal foil 10 having gold foil as the first metal layer 11, gold foil as the second metal layer 12, and five layers of silver foil as the third metal layer 13.

[0079] The materials of the first metal layer 11, the second metal layer 12, and the third metal layer 13 may be thin metal films formed by thin film formation methods such as vapor deposition and sputtering, or may be commercially available metal foils or clear metals such as gold foil, silver foil, silver glazing, and copper glazing.

[0080] [Conductive filler] The conductive filler according to the present invention is the metal fine particles 100 made of the multilayer metal foil 10 described above. The conductive filler has excellent chemical stability and is suitable for reducing raw material costs. The conductive filler also has excellent oxidation resistance.

[0081] The metal microparticles 100 are obtained by microparticulating the multilayer metal foil 10. The method of microparticulation is not particularly limited. For example, the multilayer metal foil 10 may be mixed with glue or starch syrup, stirred and pulverized, washed with a large amount of water to remove the glue or starch syrup, and then dried to obtain a powder (powdered).

[0082] In metal microparticle 100, it is preferable that the chemical stability of first metal layer 11 and the chemical stability of second metal layer 12 are higher than the chemical stability of third metal layer 13.

[0083] In the metal microparticles 100, the chemical stability of the first metal layer 11 and the second metal layer 12 constituting the main surfaces 10a and 10b is higher than that of the third metal layer 13, so that the chemical stability of the metal microparticles 100 as a conductive filler can be improved. Examples of the metal microparticles 100 having such a configuration include metal microparticles 100 made of a multilayer metal foil 10 using gold as the metals M1 and M2 and silver or copper as the metal M3, metal microparticles 100 made of a multilayer metal foil 10 using silver as the metals M1 and M2 and copper as the metal M3, and metal microparticles 100 made of a multilayer metal foil 10 using gold as the metal M1, silver as the metal M2, and copper as the metal M3.

[0084] In the present disclosure, the chemical stability of the metal foil (metal layer) in the metal microparticles 100 can be evaluated by the method described below based on the sheet resistance of the conductive film containing the metal microparticles 100. The sheet resistance (Ω / sq) in the film surface direction of the conductive film to be measured can be measured by the four-probe method using a low resistivity meter. First, the sheet resistance of the conductive film is measured in air at room temperature, and this is taken as the initial resistance ρ0. Next, the conductive film is stored in air at room temperature for n days (20≦n≦100). The sheet resistance of the conductive film after storage for n days is measured, and this is taken as the resistance ρ n The sheet resistance of the conductive film may be measured multiple times at regular intervals over n days. For example, the sheet resistance of the conductive film may be measured three times every 20 days over a 60-day period. |ρ n The smaller the value represented by |-ρ0|, the less the change in sheet resistance of the conductive film over time and the higher the chemical stability. For example, the chemical stability of gold is higher than that of silver and copper. The chemical stability of silver is higher than that of copper.

[0085] As described above, the chemical stability of the metal foil (metal layer) in the metal microparticles 100 can also be evaluated based on the standard electrode potential of the metal foil (metal layer). The higher the standard electrode potential, the higher the chemical stability can be considered to be.

[0086] In metal microparticle 100, electrical conductivity σ11 of first metal layer 11 and electrical conductivity σ12 of second metal layer 12 may be lower than electrical conductivity σ13 of third metal layer 13.

[0087] When the electrical conductivity σ11 and the electrical conductivity σ12 are lower than the electrical conductivity σ13, the electrical conductivity of the conductive filler can be improved by the high electrical conductivity σ13 of the third metal layer 13. An example of the metal microparticle 100 having such a configuration is a metal microparticle 100 made of a multilayer metal foil 10 using gold as the metal M1 and the metal M2, and silver or copper as the metal M3.

[0088] In the present disclosure, the conductivity of the metal foil (metal layer) in the metal microparticles 100 can be evaluated based on the sheet resistance (initial resistance ρ0) of the conductive film containing the above-mentioned metal microparticles 100. The smaller the sheet resistance, the higher the conductivity of the conductive film can be considered to be. For example, the sheet resistances (initial resistance ρ0) of the No. 4 color gold foil, the three-step color gold foil, and the fixed color gold foil (see Table 1) used in the examples described later are 0.46 Ω / sq, 0.74 Ω / sq, and 0.78 Ω / sq, respectively. The sheet resistance (initial resistance ρ0) of the silver foil (see Table 2) used in the examples described later is 0.09 Ω / sq.

[0089] In the metal microparticle 100, the electrical conductivity σ11 of the first metal layer 11 and the electrical conductivity σ12 of the second metal layer 12 may be higher than the electrical conductivity σ13 of the third metal layer 13. An example of the metal microparticle 100 having such a configuration is a metal microparticle 100 made of a multilayer metal foil 10 using silver as the metal M1 and the metal M2 and copper as the metal M3.

[0090] The thickness of the metal microparticles 100 is the same as the thickness t10 of the above-mentioned multilayer metal foil 10. That is, the thickness of the metal microparticles 100 is preferably 100 nm or more and 10 μm or less.

[0091] The metal particles 100 have an area of ​​3 to 70 μm 2 The area of ​​the main surface of the metal microparticle 100 is preferably 5 μm 2Above that, another 7μm 2 It may be more than 50 μm 2 Below 40μm 2 Below, especially 30 μm 2 Below, especially 20 μm 2 Less than 15 μm is preferable, and in some cases 2 It may be the following.

[0092] The thickness of the metal microparticle 100 can be obtained by measuring the thickness at 10 points in a TEM image using a transmission electron microscope (TEM) and calculating the simple average. The area of ​​the main surface of the metal microparticle 100 can be obtained by measuring the areas of 100 metal microparticles 100 included in an SEM image using a scanning electron microscope (SEM) and calculating the simple average.

[0093] The ratio of the long side to the short side of the main surface of the metal microparticle 100 is preferably 20 or less, particularly 10 or less. Here, the long side and short side of the main surface are the longest and shortest sides set on the main surface so as to pass through the center of gravity of the main surface. The above ratio, like the above area, can be determined by measuring the ratio of the long side to the short side of the main surface of at least 30, preferably 100, metal microparticles 100 using SEM and calculating the simple average.

[0094] [Conductive materials] The conductive material according to the present invention includes the conductive filler described above. The conductive material has excellent chemical stability and is suitable for reducing raw material costs. The conductive material also has excellent oxidation resistance. The conductive material is, for example, a conductive ink or a conductive film obtained by drying the conductive ink.

[0095] (Conductive ink) The conductive ink contains inorganic compound particles and / or insulating resin particles in addition to the above-mentioned conductive filler (metallic particles 100).

[0096] The inorganic compound particles do not need to have high electrical conductivity like the metal particles 100, and have a resistivity of 1×10-4 Ω cm or more, and even 1×10 -3 Ω cm or more, especially 1×10 6 The inorganic compound particles may be made of a material having a resistivity of Ω·cm or more. The inorganic compound particles may be made of an insulator, or may be made of a semiconductor such as ITO or AZO. The inorganic compound constituting the inorganic compound particles may be an oxide, nitride, carbide, etc. However, alloys that are not compounds are excluded from inorganic compounds. The insulating resin particles have a resistivity of 1×10 at 20°C. 6 The insulating resin particles may be made of a material having a resistivity of Ω·cm or more. The resin constituting the insulating resin particles may be an acrylic resin, a silicone resin, a styrene resin, a polyamide resin, or the like.

[0097] The preferred fine particles to be added as solids are inorganic compound fine particles, particularly oxide fine particles. Oxide fine particles have the advantage of being more heat resistant than resin fine particles. The oxide fine particles may contain at least one selected from silicon oxide, titanium oxide, zinc oxide, tin oxide, zirconium oxide, cerium oxide, tantalum oxide, aluminum oxide, calcium oxide, magnesium oxide, and molybdenum oxide, and preferably contain silicon oxide. Silicon oxide fine particles are commercially available as colloidal silica, etc., and are easily and inexpensively available.

[0098] The shape of the inorganic compound fine particles and insulating resin fine particles is not particularly limited, and may be spherical, ellipsoidal, cylindrical, conical, polyhedral, etc. The fine particles may be in the form of a foil, and in this case, the value Rp obtained by dividing the square root of the area of ​​the main surface by the thickness is preferably smaller than the value Rg of gold fine particles calculated in the same manner, and more preferably less than half the value Rg of gold fine particles. For example, when the area is 36 μm 2 The foil-like fine particles used together with metal fine particle 100 having a main surface of 100 nm and a thickness of 150 nm preferably have the above-mentioned value Rp for their shape of less than 40, and more preferably 20 or less.

[0099] The particle size of the inorganic compound fine particles and insulating resin fine particles is not particularly limited, but may be 1 nm to 500 μm, further 10 to 1000 nm, particularly 10 to 500 nm. The particle size of the fine particles can be determined by measuring the particle sizes of at least 30 particles, preferably 100 particles, using a scanning electron microscope (SEM) or the like, and calculating the simple average. The particle size of each fine particle is the average value of its minimum and maximum diameters.

[0100] In the conductive film, the foil-like metal particles 100 are usually oriented so that their main surfaces are aligned along the film surface direction to form a conductive path in the film. The inorganic compound particles and insulating resin particles can improve the orientation of the metal particles 100 and promote the formation of the conductive path. The solid content of the conductive film can also be supplied as a solute in the conductive ink, rather than as fine particles. However, in order to improve the orientation of the foil-like metal particles 100, it is suitable to add the solid content to the conductive ink as fine particles.

[0101] The conductive ink may further contain solids other than the fine particles, in addition to the metal fine particles 100, the inorganic compound fine particles and / or the insulating resin fine particles. The solids preferably contain a resin added to the ink as a solute. Examples of preferred resins are water-soluble resins such as polyvinyl alcohol, polyethylene oxide, polyethylene glycol, polyacrylamide, carboxymethyl cellulose, polyvinylpyrrolidone, and sodium polyacrylate. However, it is desirable to adjust the content of the resin supplied as the solute to be less than the total content of the inorganic compound fine particles and / or the insulating resin fine particles, particularly 1 / 2 or less, and even 1 / 10 or less of this total content, on a mass basis.

[0102] The conductive ink may contain a resin precursor. The resin precursor is, for example, a monomer of a polymer constituting the resin. In this specification, a component (e.g., a monomer) that is contained in the conductive ink in a form different from the solid content (e.g., a polymer) contained in the conductive film and that can supply the solid content of the conductive film is also treated as a solid content contained in the conductive ink.

[0103] The conductive ink may contain conductive resin particles. However, even in this case, it is desirable to adjust the content of the conductive resin particles to be less than the total content of the inorganic compound particles and / or the insulating resin particles, particularly 1 / 2 or less, and further 1 / 10 or less of the total content, by mass. The conductive ink may not contain conductive resin particles, and specifically may not contain PEDOT:PSS.

[0104] In the conductive ink, the dispersion medium for dispersing the metal particles 100 is preferably water. However, an organic solvent can also be used as the dispersion medium. The dispersion medium can also function as a solvent for dissolving at least a part of the resin and other components.

[0105] As with conventional conductive inks, lubricants, viscosity adjusters, surfactants, particle protectors, stabilizers, and other ingredients can be added to the conductive ink as needed. When a monomer is added as a resin precursor, it is desirable to add a polymerization initiator. A preferred polymerization initiator is a photopolymerization initiator. When a photopolymerization initiator is added, a photopolymerization accelerator, a sensitizer, etc. may also be added together.

[0106] In the conductive ink, the content of the metal microparticles 100 is preferably 0.15% by mass or more, more preferably 0.25% by mass or more, and particularly preferably 0.375% by mass or more, based on the total amount of the conductive ink. When a low resistance value is to be imparted to the conductive film, a value exceeding 0.5% by mass, for example 0.75% by mass or more, is suitable. However, an increase in raw material cost due to excessive addition of the metal microparticles 100 may cancel out the advantage of a decrease in the resistance value of the conductive film. Therefore, the content of the metal microparticles 100 may be 15% by mass or less, more preferably 5% by mass or less, and particularly preferably 2% by mass or less, based on the total amount of the conductive ink, and may be 1.5% by mass or less, or even 1% by mass or less in some cases. When the resistance value required for the conductive film is not so low, the content may be 0.5% by mass or less.

[0107] The content of the metal microparticles 100, expressed as the solid content ratio of the conductive ink (ratio to the total solid content), is desirably 15% by mass or more, 20% by mass or more, or even 30% by mass or more, and 45% by mass or more is suitable when a low resistance value is to be imparted to the conductive film. However, an increase in raw material cost due to excessive addition of the metal microparticles 100 may cancel out the advantage of a decrease in the resistance value of the conductive film. Therefore, the content of the metal microparticles 100, expressed as the solid content ratio of the conductive ink, may be less than 80% by mass, or even less than 75% by mass, and may be less than 50% by mass when used for applications that do not require a sufficiently low resistance value. Here, the "solid content" refers to components that can constitute the conductive film, specifically including fine particles and resins, and excluding the dispersion medium, which is a volatile component.

[0108] The total content of inorganic compound microparticles and / or insulating resin microparticles is desirably 0.15 mass% or more, preferably 0.25 mass% or more, and particularly desirably 0.5 mass% or more, relative to the total amount of the conductive ink, and is desirably 50 mass% or less, preferably 10 mass% or less, and particularly desirably 1 mass% or less.

[0109] (Conductive film) FIG. 4 shows a schematic cross-sectional view of an example of the conductive film according to the present invention. The conductive film 1 shown in FIG. 4 contains metal fine particles 100, which are conductive fillers, and solid content 200 other than the metal fine particles 100. The conductive film 1 has conductive paths 15 constituted by a plurality of metal fine particles 100 in contact with each other. The conductive paths 15 extend in the film surface direction of the conductive film 1. The conductive film 1 has, together with the conductive paths 15, one or more protective layers 14 that support the conductive paths 15 on the substrate 2 side of the film 1 or cover the conductive paths 15 on the surface side of the film 1. The protective layer 14 contains solid content 200. The conductive film 1 can be formed by applying the above-mentioned conductive ink onto the substrate 2.

[0110] The solid content 200 includes inorganic compound fine particles and / or insulating resin fine particles. However, in FIG. 4, the outer shapes of the individual fine particles constituting the solid content 200 are omitted. The solid content 200 may be mainly composed of inorganic compound fine particles and / or insulating resin fine particles in contact with each other, or may be composed of fine particles in contact with each other. The solid content 200 may include a material such as a resin supplied as a solute from the conductive ink. The solid content 200 may include conductive resin fine particles, but may not include conductive resin fine particles, specifically, may not include PEDOT:PSS.

[0111] The conductive film 1 may contain metal fine particles 100x that do not form a conductive path 15. FIG. 5 is a schematic cross-sectional view of another example of the conductive film according to the present invention. As shown in FIG. 5, the conductive film 1 may contain multiple conductive paths 15. The thickness of the conductive path 15 may be less than 50% of the thickness of the conductive film 1, or even 30% or less. When multiple conductive paths 15 are present, the thickness of the conductive path 15 is defined as the sum of the thicknesses of the paths 15. The thickness of the protective layer 14 may be greater than the thickness of the conductive path 15. When multiple protective layers 14 are present, the thickness of the protective layer 14 is defined as the sum of the thicknesses of the layers 14.

[0112] Unlike FIG. 6 described later, in FIGS. 4 and 5, the majority of the metal microparticles 100 are oriented so that their main surfaces are approximately parallel to the film surface. Here, "approximately parallel to the film surface" refers to an angle θ between a perpendicular line 21 to the main surface 100a and the thickness direction T of the film being less than 45 degrees, preferably 40 degrees or less, and more preferably 35 degrees or less, as shown in FIGS. 7A and 7B. If the main surface 100a is not flat (see FIG. 7B), the angle θ varies depending on the position where the perpendicular line 21 is drawn. In consideration of this, when measuring the angle θ, the perpendicular line 21 is set to pass through the center 100c of the main surface 100a facing the surface side of the film when the cross section of the metal microparticle 100 is observed. The thickness direction T of the film is, to be precise, a direction perpendicular to the bottom surface 16 of the film 1 in contact with the substrate 2. The orientation of the metal microparticles 100 can be obtained by observing the cross section of the metal microparticles 100 using an SEM or the like. The orientation is also desirably determined by measuring at least 30 metal microparticles 100, and preferably 100 metal microparticles 100.

[0113] The substantially parallel orientation of the metal microparticles 100 is suitable for forming the conductive paths 15 with a small amount of metal microparticles 100. Therefore, in the conductive film 1, it is preferable that 70% or more, preferably 80% or more, and more preferably 90% or more of the metal microparticles 100 are oriented substantially parallel to the film surface. When 70% or more of the metal microparticles 100 are oriented substantially parallel to the film surface, it becomes possible to form the conductive paths 15 even if the content of the metal microparticles 100 in the conductive film 1 is as low as less than 80% by mass, further less than 75% by mass, and in some cases less than 50% by mass.

[0114] Fig. 6 is a schematic cross-sectional view for explaining the dispersion state of the conductive filler in the film. In the film 1 of Figs. 4 and 5, all of the metal fine particles 100 are oriented approximately parallel to the film surface. In contrast, in the film 3 of Fig. 6, metal fine particles 101 oriented approximately parallel to the film surface and metal fine particles 102 not oriented approximately parallel to the film surface are present, and the ratio of metal fine particles 101 to all metal fine particles 101, 102 remains in a low range. In the state of Fig. 6, it is not easy for a small amount of metal fine particles 101, 102 to form a conductive path.

[0115] The preferred shape of the metal microparticle 100 is as described above. Specifically, the thickness is 100 nm to 10 μm and the area is 3 to 70 μm. 2 The thickness of the foil is 100 nm to 10 μm and the area is 3 to 40 μm. 2 The foil shape having a principal surface that is 0.1 to 1.0 mm is particularly suitable for efficiently forming conductive paths 15 in a conductive film 1 in which the content of metal fine particles 100 is less than 50 mass %.

[0116] The sheet resistance of the conductive film 1 is determined according to the configuration of the metal fine particles 100 (multilayer metal foil 10), and is, for example, 1000Ω / sq or less, further 100Ω / sq or less, particularly 30Ω / sq or less, and especially 20Ω / sq or less. The conductive film 1 may have a sheet resistance of 7Ω / sq ​​or less, 5Ω / sq or less, further 3Ω / sq or less, particularly 1Ω / sq or less, and in some cases 0.8Ω / sq or less. Although it is possible to have such a low sheet resistance, the conductive film 1 can be formed without heating to a high temperature or a reduced pressure atmosphere. The lower limit of the sheet resistance is not particularly limited, and is, for example, 0.01Ω / sq or more. The lower limit of the sheet resistance may be 0.05Ω / sq or more, 0.1Ω / sq or more, or even 0.3Ω / sq or more. EXAMPLES

[0117] The present invention will be described in more detail below with reference to examples, but the following examples are not intended to limit the present invention.

[0118] [material] In this example, gold foil, silver foil, silver-clarified, and copper-clarified were used as materials for the multilayer metal foil. The type, composition, size, and raw material cost of the gold foil used as the material in this example are shown in Table 1. The composition, size, and raw material cost of the silver foil and silver-clarified used as the material in this example are shown in Table 2. The composition, size, and raw material cost of the copper-clarified used as the material in this example are shown in Table 3. Tables 1 to 3 are based on the alloy ratios specified by the Ishikawa Prefecture Foil Commerce and Industry Cooperative. The materials in Tables 1 to 3 are commercially available.

[0119] [Table 1]

[0120] [Table 2]

[0121] [Table 3]

[0122] [Structural evaluation method for multilayer metal foil] The thickness t10 of the multilayer metal foil produced in this embodiment and the thickness t13 of the third metal layer included in the multilayer metal foil were measured using a TEM. Specifically, for any one multilayer metal foil, the thicknesses of the multilayer metal foil at 8 to 12 points in the TEM image and the thicknesses of the third metal layer included in the multilayer metal foil were measured and calculated as a simple average. The thickness t11 of the first metal layer and the thickness t12 of the second metal layer included in the multilayer metal foil were calculated as {(t10-t13) / 2}. Note that, since each thickness is rounded off to the nearest whole number, the value calculated as (t11+t12+t13) may not match t10.

[0123] [Preparation of multi-layer metal foil] As described below, the multilayer metal foils of Examples 1 to 6 were produced. In the multilayer metal foils of Examples 1 to 6, silver-finished product was used as the material of the third metal layer.

[0124] Example 1 Constant color gold foil was used as the material for the first metal layer and the second metal layer. Ginsei was used as the material for the third metal layer. Using these materials, the multilayer metal foil of Example 1 was obtained by the above-mentioned manufacturing method of the multilayer metal foil. Specifically, Ginsei was placed between two sheets of constant color gold foil to obtain a laminate. Next, the laminate was beaten out to a thickness of 205 nm. In this way, the multilayer metal foil of Example 1 was produced. The evaluation results of the multilayer metal foil of Example 1 are shown in Table 4.

[0125] Example 2 After obtaining the laminate, the laminate was stretched to a thickness of 119 nm. Except for this, the multilayer metal foil of Example 2 was obtained in the same manner as in Example 1. The evaluation results of the multilayer metal foil of Example 2 are shown in Table 4.

[0126] Example 3 Three-tone gold foil was used as the material for the first metal layer and the second metal layer. After obtaining the laminate, the laminate was rolled out to a thickness of 299 nm. Except for these, the multilayer metal foil of Example 3 was obtained in the same manner as in Example 1. The evaluation results of the multilayer metal foil of Example 3 are shown in Table 4.

[0127] Example 4 After obtaining the laminate, the laminate was stretched to a thickness of 174 nm. Except for this, the multilayer metal foil of Example 4 was obtained in the same manner as in Example 3. The evaluation results of the multilayer metal foil of Example 4 are shown in Table 4.

[0128] Example 5 No. 4 color gold foil was used as the material for the first metal layer and the second metal layer. After obtaining the laminate, the laminate was rolled out to a thickness of 275 nm. Except for these, the multilayer metal foil of Example 5 was obtained in the same manner as in Example 1. The evaluation results of the multilayer metal foil of Example 5 are shown in Table 4.

[0129] Example 6 After obtaining the laminate, the laminate was stretched to a thickness of 134 nm. Except for this, the multilayer metal foil of Example 6 was obtained in the same manner as in Example 5. The evaluation results of the multilayer metal foil of Example 6 are shown in Table 4.

[0130] [Table 4]

[0131] As described below, the multilayer metal foils of Examples 7 to 15 were produced. In the multilayer metal foils of Examples 7 to 15, five sheets of silver foil were used as the material for the third metal layer.

[0132] Example 7 A constant color gold foil was used as the material for the first metal layer and the second metal layer. Five sheets of silver foil were stacked and used as the material for the third metal layer. Using these materials, the multilayer metal foil of Example 7 was obtained by the above-mentioned manufacturing method of the multilayer metal foil. Specifically, five sheets of silver foil were stacked and arranged between two sheets of constant color gold foil to obtain a laminate. Next, the laminate was beaten out to a thickness of 368 nm. In this way, the multilayer metal foil of Example 7 was produced. The evaluation results of the multilayer metal foil of Example 7 are shown in Table 5.

[0133] Example 8 After obtaining the laminate, the laminate was stretched to a thickness of 263 nm. Except for this, the multilayer metal foil of Example 8 was obtained in the same manner as in Example 7. The evaluation results of the multilayer metal foil of Example 8 are shown in Table 5.

[0134] Example 9 After obtaining the laminate, the laminate was stretched to a thickness of 88 nm. Except for this, the multilayer metal foil of Example 9 was obtained in the same manner as in Example 7. The evaluation results of the multilayer metal foil of Example 9 are shown in Table 5.

[0135] Example 10 Three-tone gold foil was used as the material for the first metal layer and the second metal layer. After obtaining the laminate, the laminate was rolled out to a thickness of 321 nm. Except for these, the multilayer metal foil of Example 10 was obtained in the same manner as in Example 7. The evaluation results of the multilayer metal foil of Example 10 are shown in Table 5.

[0136] Example 11 After obtaining the laminate, the laminate was stretched to a thickness of 270 nm. Except for this, the multilayer metal foil of Example 11 was obtained in the same manner as in Example 10. The evaluation results of the multilayer metal foil of Example 11 are shown in Table 5.

[0137] Example 12 After obtaining the laminate, the laminate was stretched to a thickness of 141 nm. Except for this, the multilayer metal foil of Example 12 was obtained in the same manner as in Example 10. The evaluation results of the multilayer metal foil of Example 12 are shown in Table 5.

[0138] (Example 13) No. 4 color gold foil was used as the material for the first metal layer and the second metal layer. After obtaining the laminate, the laminate was beaten out to a thickness of 291 nm. Except for these, the multilayer metal foil of Example 13 was obtained in the same manner as in Example 7. The evaluation results of the multilayer metal foil of Example 13 are shown in Table 5.

[0139] Example 14 After obtaining the laminate, the laminate was stretched to a thickness of 203 nm. Except for this, the multilayer metal foil of Example 14 was obtained in the same manner as in Example 13. The evaluation results of the multilayer metal foil of Example 14 are shown in Table 5.

[0140] Example 15 After obtaining the laminate, the laminate was stretched to a thickness of 156 nm. Except for this, the multilayer metal foil of Example 15 was obtained in the same manner as in Example 13. The evaluation results of the multilayer metal foil of Example 15 are shown in Table 5.

[0141] [Table 5]

[0142] As described below, the multilayer metal foils of Examples 16 to 19 were produced. In the multilayer metal foils of Examples 16 to 19, clear copper was used as the material for the third metal layer.

[0143] Example 16 A constant color gold foil was used as the material for the first metal layer and the second metal layer. A copper foil was used as the material for the third metal layer. Using these materials, the multilayer metal foil of Example 16 was obtained by the above-mentioned manufacturing method of the multilayer metal foil. Specifically, the copper foil was placed between two sheets of constant color gold foil to obtain a laminate. Next, the laminate was beaten out to a thickness of 233 nm. In this way, the multilayer metal foil of Example 16 was produced. The evaluation results of the multilayer metal foil of Example 16 are shown in Table 6.

[0144] (Example 17) Three-tone gold foil was used as the material for the first metal layer and the second metal layer. After obtaining the laminate, the laminate was rolled out to a thickness of 380 nm. Except for these, the multilayer metal foil of Example 17 was obtained in the same manner as in Example 16. The evaluation results of the multilayer metal foil of Example 17 are shown in Table 6.

[0145] (Example 18) No. 4 color gold foil was used as the material for the first metal layer and the second metal layer. After obtaining the laminate, the laminate was rolled out to a thickness of 333 nm. Except for these, the multilayer metal foil of Example 18 was obtained in the same manner as in Example 16. The evaluation results of the multilayer metal foil of Example 18 are shown in Table 6.

[0146] (Example 19) Silver foil was used as the material for the first metal layer and the second metal layer. After obtaining the laminate, the laminate was stretched to a thickness of 216 nm. Except for these, the multilayer metal foil of Example 19 was obtained in the same manner as in Example 16. The evaluation results of the multilayer metal foil of Example 19 are shown in Table 6.

[0147] [Table 6]

[0148] The fixed color gold foil, three-step color gold foil, and No. 4 color gold foil shown in Table 1 were used as the metal foils of Reference Examples 1, 2, and 3, respectively. The silver foil shown in Table 2 was used as the metal foil of Reference Example 4. The configurations, metal contents, and raw material costs of the metal foils of Reference Examples 1 to 4 and Examples 2, 4, 6, 9, 12, and 15 to 19 are shown in Table 7. The metal contents (mass%) were determined from the thicknesses and alloy densities of each metal foil shown in Tables 4 to 6. The alloy densities of each gold foil were: fixed color: 14.35 g / cm 3 , Sanpo color: 16.03g / cm 3 , No. 4 color: 18.42g / cm 3 The raw material cost was calculated using the metal content according to the following steps (1) to (5). The price of each metal was set as follows: gold: 8,500 yen / g, silver: 117.7 yen / g, copper: 1.17 yen / g. The volume of each metal foil was calculated based on the surface area of ​​1 cm. 2 It was decided. (1) Mass of the third metal layer: thickness (cm) x 1 cm 2 × Alloy density (g / cm 3 ) (2) Total mass of the first metal layer and the second metal layer: {thickness (cm) x 1 cm 2 × Alloy density (g / cm 3 )}×2 (3) Mass of each metal contained in the metal foil: (2) x alloy composition of the metal foil (Tables 1 to 3) (4) Metal content: (3) / ((1)+(2))} (5) Raw material cost: Calculate the metal content x price for each element.

[0149] [Table 7]

[0150] Figures 8 to 26 show the results of TEM observation (300,000 to 1,000,000 magnifications) of the cross sections of the multilayer metal foils of Examples 1 to 19. Figures 27 to 37 show the results of observation of the main surfaces of the multilayer metal foils of Examples 1 to 19. Note that Figures 27 to 37 correspond to Figures 20 to 30 of the previous application. For Figures 27 to 37, color drawings were submitted as exhibits at the same time as this application so that the differences in color tones of the main surfaces of the multilayer metal foils of Examples 1 to 19 can be understood.

[0151] 《Consideration》 In the multilayer metal foils of Examples 1 to 18, gold foil is used as the material of the first metal layer and the second metal layer, so that improvement in chemical stability and improvement in oxidation resistance are expected. In addition, as shown in Table 7, in the examples in which gold foil or silver foil is used as the material of the first metal layer and the second metal layer, and silver-finished, multiple silver foils, or copper-finished is used as the material of the third metal layer, the raw material cost can be reduced compared to Reference Examples 1 to 3 in which only gold foil is used. In particular, in Example 19 in which silver foil is used as the material of the first metal layer and the second metal layer, and copper-finished is used as the material of the third metal layer, the raw material cost can be reduced compared to Reference Example 4 in which only silver foil is used. Furthermore, as shown in Figures 27 to 37, the color expressed on the main surface of the multilayer metal foil can be changed in various ways by combining the first metal layer, the second metal layer, and the third metal layer.

[0152] [Preparation of conductive film] Metal microparticles were prepared by microparticulating the multilayer metal foils of Examples 1 to 11 and 13 to 14, the gold foils of Reference Examples 1 to 3, and the silver foil of Reference Example 4. A predetermined amount of metal microparticles was mixed with an equal amount of a mixture of a PEDOT:PSS solution (Clevios (registered trademark) PH1000; manufactured by Heraeus) and pure water to prepare a conductive ink. The solid content of the PEDOT:PSS solution used was 1.0 to 1.3 mass%, and the solvent was water. 1 mL of the conductive ink was dropped onto a glass substrate, and a conductive film was formed by a casting method. The formed conductive film was dried at 40°C and 60°C for 1 hour using a hot plate, and then heat-treated at 130°C for 30 minutes. As a result, a conductive film containing a predetermined amount of metal microparticles was obtained from the metal foils of Examples 1 to 11, 13 to 14, and Reference Examples 1 to 4. Table 8 shows the correspondence between the conductive film and the metal foil used to prepare the metal microparticles contained therein. The heat treatment at 130° C. was carried out in order to completely remove moisture in a short period of time, and the formation of the conductive film itself is possible without this treatment.

[0153] [Table 8]

[0154] [Evaluation of the conductivity of conductive films] The sheet resistance in the film surface direction of the conductive films of Examples 20 to 32 and Reference Examples 5 to 8 was measured by a four-probe method using a low resistivity meter (Loresta GX, MCP-T700; manufactured by Nitto Seiko Analytech Co., Ltd.). Figures 38 to 43 show the sheet resistance of the conductive films of Examples 20 to 32 together with the content of metal fine particles in the conductive ink used to prepare the conductive films. Figure 44 shows the sheet resistance of the conductive films of Reference Examples 5 to 8 together with the content of metal fine particles in the conductive ink used to prepare the conductive films.

[0155] 38 to 44, the horizontal axis indicates the content (mass%) of metal particles in the conductive ink used to produce the conductive film. Note that 0.5 mass% and 1 mass% on the horizontal axis roughly correspond to 43 to 50 mass% and 61 to 67 mass% when converted into the solid content ratio of the conductive ink. This solid content ratio corresponds to the content of metal particles in the conductive film.

[0156] Table 9 shows the sheet resistance of the conductive films of Reference Examples 5 to 8 and Examples 21, 23, and 25 when the content of metal particles contained in the conductive ink used to prepare the conductive films was approximately the same.

[0157] [Table 9]

[0158] 《Consideration》 As shown in Figures 38 to 44, the sheet resistance of the conductive film showed a tendency to decrease with an increase in the metal fine particles. As shown in Table 9, when the content of the metal fine particles was about the same, the conductive film of the Example showed a significantly lower sheet resistance than the conductive film of the Reference Example, and showed excellent conductivity. Furthermore, the conductive film of the Example showed a sheet resistance reduced to about half that of the conductive film of Reference Examples 5 to 7, which used only gold foil as the metal fine particles. In particular, the conductive films of Examples 21, 23, and 25 showed a lower sheet resistance than Reference Example 5, which used only constant-color gold foil as the metal fine particles. Note that, as can be seen from a comparison between Examples 20 to 25 in Figures 38 to 40 and Examples 26 to 32 in Figures 41 to 43, the conductivity of the conductive film of Examples 26 to 32, which used five sheets of silver foil as the material for the third metal layer of the metal fine particles, showed almost the same tendency as the conductivity of the conductive film of Examples 20 to 25, which used silver clear as the material for the third metal layer of the metal fine particles. In other words, no significant difference was observed in the sheet resistance depending on the structure of the third metal layer.

[0159] [Evaluation of the chemical stability of conductive films] A conductive film having a metal fine particle content of 0.3 mass% in Reference Example 1 was prepared, and this was used as the conductive film of Reference Example 9. A conductive film having a metal fine particle content of 1.0 mass% in Reference Example 1 was prepared, and this was used as the conductive film of Reference Example 10. A conductive film having a metal fine particle content of 0.3 mass% in Reference Example 3 was prepared, and this was used as the conductive film of Reference Example 11. A conductive film having a metal fine particle content of 1.0 mass% in Reference Example 3 was prepared, and this was used as the conductive film of Reference Example 12. Table 10 shows the configurations and metal fine particle contents of the conductive films of Reference Examples 9 to 12.

[0160] [Table 10]

[0161] The conductive films of Reference Examples 9 to 12 were evaluated for the change over time in sheet resistance by the above-mentioned method. Specifically, first, the sheet resistance of the conductive film was measured, and this was taken as the initial resistance. Next, the conductive film was stored in the air at room temperature, and the sheet resistance was measured at regular intervals. The results are shown in FIG.

[0162] 《Consideration》 As shown in Figure 45, no significant change was observed in the sheet resistance of the conductive film up to about 60 days. From this result, good chemical stability was confirmed even when fixed color gold leaf, which has a lower gold content than No. 4 color gold leaf, was used as the material for the metal particles contained in the conductive film.

[0163] Next, metal fine particles were prepared using the multilayer metal foils of Examples 1, 3, and 5, and the conductive films of Examples 33, 34, and 35 were prepared in the same manner as the conductive films of Examples 20, 22, and 24. That is, the conductive films of Examples 33, 34, and 35 had the same configuration as the conductive films of Examples 20, 22, and 24. The conductive films of Examples 33, 34, and 35 were evaluated for conductivity in the same manner as described above. FIG. 46 shows the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive film of Example 33 and the sheet resistance of the conductive film of Example 33, together with Reference Examples 5 and 8. FIG. 47 shows the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive film of Example 34 and the sheet resistance of the conductive film of Example 34, together with Reference Examples 6 and 8. FIG. 48 shows the relationship between the content of metal fine particles in the conductive ink used to prepare the conductive film of Example 35 and the sheet resistance of the conductive film of Example 35, together with Reference Examples 7 and 8.

[0164] 《Consideration》 As can be seen from the comparison between Example 33 in FIG. 46 and Example 20 in FIG. 38, the sheet resistance of the conductive film of Example 33 showed almost the same tendency as the sheet resistance of the conductive film of Example 20 having the same configuration. As can be seen from the comparison between Example 34 in FIG. 47 and Example 22 in FIG. 39, the sheet resistance of the conductive film of Example 34 showed almost the same tendency as the sheet resistance of the conductive film of Example 22 having the same configuration. As can be seen from the comparison between Example 35 in FIG. 48 and Example 24 in FIG. 40, the sheet resistance of the conductive film of Example 35 showed almost the same tendency as the sheet resistance of the conductive film of Example 24 having the same configuration. From these results, it was confirmed that the multilayer metal foil of the present invention has good reproducibility.

[0165] Furthermore, from Figures 46 to 48, it can be seen that the conductive films of the examples in which Ginsei was used as the material for the third metal layer used to prepare the metal microparticles showed lower sheet resistance than the reference examples in which only No. 4 color gold foil, three-step color gold foil, and fixed color gold foil were used as the material for the metal microparticles, and the reference example in which only silver foil was used as the material for the metal microparticles, and showed particularly excellent electrical conductivity. [Industrial Applicability]

[0166] The present invention has great industrial value in that it promotes the industrial use of gold foil, a metal foil whose main component is gold, i.e., gold foil, which has previously been used primarily in the field of arts and crafts, for example, as a material for electrodes in various devices. [Explanation of symbols]

[0167] 10 Multilayer metal foil 10a,10b main surface 11 1st metal layer 12 Second metal layer 13 Third metal layer 100,100x,101,102 Metal fine particles 200 Solid content of inorganic compounds and / or insulating resins, etc. 1. Conductive film 2. Board 14 Protective layer 15 Conductive Path 21 Perpendicular to the principal surface

Claims

1. a first metal layer, a second metal layer, and a third metal layer disposed between the first metal layer and the second metal layer; a metal contained as a main component in the second metal layer is the same as or different from a metal contained as a main component in the first metal layer; a metal contained as a main component in the third metal layer is different from the metal contained as a main component in the first metal layer and the metal contained as a main component in the second metal layer; Multilayer metal foil.

2. 2. The multilayer metal foil according to claim 1, wherein the standard electrode potential of the metal contained as a main component in the first metal layer and the metal contained as a main component in the second metal layer is greater than the standard electrode potential of the metal contained as a main component in the third metal layer.

3. The multilayer metal foil according to claim 1 , wherein the first metal layer and the second metal layer satisfy one selected from the group consisting of the following (I) to (III): (I) The metal contained as a main component in the first metal layer and the metal contained as a main component in the second metal layer are gold. (II) The metal contained as a main component in the first metal layer and the metal contained as a main component in the second metal layer are silver. (III) The metal contained as a main component in the first metal layer is gold, and the metal contained as a main component in the second metal layer is silver.

4. The multilayer metal foil according to claim 3 , wherein the third metal layer satisfies the following (i) or (ii): (i) When the first metal layer and the second metal layer satisfy the condition (I) above, the metal contained as a main component in the third metal layer is silver or copper. (ii) When the first metal layer and the second metal layer satisfy the condition (II) or (III), the metal contained as a main component in the third metal layer is copper.

5. The multilayer metal foil according to claim 1 , wherein the metal contained as a main component in the first metal layer is the same as the metal contained as a main component in the second metal layer.

6. The multilayer metal foil according to claim 5 , wherein the content of the metal contained as a main component in the first metal layer is different from the content of the metal contained as a main component in the second metal layer.

7. The multilayer metal foil of claim 1 , wherein the third metal layer is a single layer or a multilayer.

8. The multilayer metal foil of claim 1 , wherein the thickness of said third metal layer is greater than the thickness of said first metal layer and the thickness of said second metal layer.

9. A conductive filler comprising fine metal particles formed of the multilayer metal foil according to claim 1 .

10. The conductive filler according to claim 9 , wherein in the metal fine particles, the chemical stability of the first metal layer and the chemical stability of the second metal layer are higher than the chemical stability of the third metal layer.

11. The conductive filler according to claim 10 , wherein in the metal fine particles, the conductivity of the first metal layer and the conductivity of the second metal layer are lower than the conductivity of the third metal layer.

12. The conductive filler according to claim 10 , wherein in the metal fine particles, the conductivity of the first metal layer and the conductivity of the second metal layer are higher than the conductivity of the third metal layer.

13. A conductive material comprising the conductive filler according to claim 9.

Citation Information

Patent Citations

  • Electroconductive, elastic adhesive

    JP1991217476A

  • Au / Sn composite foil and au / Sn alloy foil as well as brazing filler metal formed by using the same, method of manufacturing au / Sn composite foil, method of manufacturing au / Sn alloy foil and method of joining brazing filler metal,

    JP2002224882A

  • Electrolytic foil laminate

    JP2019186134A

  • Electroconductive composition and coating thereof

    JP2011195695A

  • Silver flake conductive paste ink with nickel particles

    JP2015157941A